Efikasi Premedikasi Klonidin dan Diazepam Peroral Terhadap Level Sedasi dan Respons Hemodinamik Pediatrik - Yudha, Sandhi; Santoso, Sugeng Budi; Murti, Bhisma (Jurnal Kedokteran Indonesia, 2012)
Background: Anxiety and pain cause emotional stress in pediatric patients. The right choice of per oral premedication is essential to achieve adequate level of sedation and hemodynamic stability during anesthesia and surgery for pediatric patients. This study aimed to compare the relative efficacy of per oral clonidine and diazepam premedication on the sedation level and hemodynamic response in pediatric patients. Methods: This was a phase II clinical trial, using double blinded randomized controlled trial design. A sample of 18 pediatric patients aged 2-12 years with ASA I and II physical status were divided at random into 2 groups, each group received either per oral clonidine premedication 4μg/kgBW (n=9) or diazepam 0.2mg/kgBW (n=9). Sedation level and hemodynamic response (heart rate) were measured before drug administration (HR1), after drug administration (HR2), before intubation laryngoscopy (HR3), third (HR4) and five minutes after (HR5) treatment before laryngoscopy intubation, immediately after skin incision started. Results: Sedation level in clonidine group (3.11 ± 0.60) was deeper than diazepam group (2.33 ± 0.50) with p=0.013. Heart rate after per oral premedication (HR1) among clonidine group was lower (100.44 ± 11.38 times/minute) than diazepam group (110.22 ± 12.29 times/minute) with p=0.099. Heart rate at time HR2, HR3, HR4, and HR 5among clonidine group was lower than diazepam group at p<0.05. Bradycardia effect was found in 2 patients in the clonidine group but none in the diazepam group. Conclusion: Per oral 4μg/kgBWclonidine premedication leads to deeper sedation level than 0.2mg/kgBWdiazepam. The hemodynamic response (heart rate) was more stable in the clonidine group than diazepam group. Keywords: Per oral premedication, clonidine, diazepam, sedation level, hemodynamic response, pediatrics